A salivary calcium‐binding protein from Laodelphax striatellus acts as an effector that suppresses defense in rice. Issue 5 (25th February 2021) - Tian, Tian; Ji, Rui; Fu, Jianmei; Li, Jing; Wang, Lu; Zhang, Hao; Yang, Shiying; Ye, Wenfeng; Fang, Jichao; Zhu‐Salzman, Keyan
Abstract: BACKGROUND: Calcium (Ca 2+ )‐binding proteins in the saliva of herbivorous insects function as effectors to attenuate host plant defenses and thus improve insect feeding performance. Silencing these genes via transgenic plant‐mediated RNAi is thus a promising pest control strategy. However, their sequences and functions in the small brown planthopper Laodelphax striatellus (SBPH) remain to be investigated. RESULTS: We identified a putative EF‐hand Ca 2+ ‐binding protein (LsECP1) in SBPH watery saliva. LsECP1 was expressed extremely high in the salivary glands but at a low level during the egg stage. Transient LsECP1 expression in rice cells indicated its cytoplasm and nucleus localization. The bacterially expressed recombinant LsECP1 protein exhibited Ca 2+ ‐binding activity. Rice plants fed by SBPH nymphs with knocked down LsECP1 exhibited higher levels of cytosolic Ca 2+, jasmonic acid (JA), jasmonoyl‐isoleucine (JA‐Ile) and hydrogen peroxide (H2 O2 ). Consistently, application of heterogeneously expressed LsECP1 protein suppressed wound‐induced JA, JA‐Ile and H2 O2 accumulation in rice. Thus, LsECP1 knockdown by dsRNA injection resulted in reduced feeding, fecundity and survival rates of SBPH reared on rice plants. Transgenic rice plants constitutively expressing LsECP1 dsRNA were produced, and plant‐mediated LsECP1 knockdown enhanced rice resistance to SBPH. CONCLUSION: SBPH LsECP1 acts as an effector to impair host rice defense responses and promotes SBPH performance. This discovery provides a potential gene target for plant‐mediated RNAi‐based pest management. © 2021 Society of Chemical Industry Abstract : The salivary effector LsECP1 of planthopper exhibits Ca 2+ ‐binding activity, and effectively suppresses plant defense response through decreasing cytosolic Ca 2+ in host plants.